Pancasila dan Etis Teologis sebagai Basis Kepemimpinan Kristen bagi Reintegrasi Iman dan Identitas Kebangsaan - Suryadi Nicolaas Napoleon Tatura; Yonatan Alex Arifianto (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2025)
Pluralistic and dynamic national life is related to the relationship between Christian faith and Pancasila values. This has an impact on leadership, which experiences complex ethical and spiritual tensions. Moral shifts and the weakening of public leaders' integrity indicate a dissonance between religious values and national spirit. Meanwhile, Christian theology is often perceived as purely spiritual, without active involvement in social and national spheres. The phenomenon of increasing identity fragmentation and moral crisis among Christian leaders emphasises the importance of reconstructing a theological basis that can integrate faith and nationalism into a single, comprehensive ethical horizon. This study aims to reinterpret Pancasila as a space for theological dialogue that shapes Christian leadership based on theological ethics for the reintegration of faith and national identity. Using qualitative methods with a literature study approach, it was concluded that Pancasila has the potential as a theological and ethical space that enables Christian leadership rooted in the values of justice and humanity. Theological ethics has proven to be a moral foundation that guides Christian leaders to integrate faith with social and national responsibilities. Thus, Pancasila-based Christian leadership serves as a means of reintegrating faith and national identity in the praxis of Indonesian public life.AbstrakKehidupan berbangsa yang plural dan dinamis, terkait relasi antara iman Kristen dan nilai-nilai Pancasila. Berdampak pada kepemimpinan yang mengalami ketegangan etis dan spiritual yang kompleks. Pergeseran moral dan melemahnya integritas pemimpin publik menunjukkan terjadinya disonansi antara nilai-nilai iman dan semangat kebangsaan. Sementara itu, teologi Kristen kerap dipersepsikan hanya bersifat spiritual, tanpa keterlibatan aktif dalam ruang sosial dan nasional. Fenomena meningkatnya fragmentasi identitas dan krisis moral di kalangan pemimpin Kristen menegaskan pentingnya rekonstruksi basis teologis yang mampu mengintegrasikan iman dan nasionalisme dalam satu horizon etis yang utuh. Penelitian ini bertujuan untuk menafsirkan kembali Pancasila sebagai ruang dialog teologis yang membentuk kepemimpinan Kristen berbasis etika teologis bagi reintegrasi iman dan identitas kebangsaan. Menggunkan metode kualitatif dengan pendekatan studi literature maka disimpulkan bahwa bahwa Pancasila memiliki potensi sebagai ruang teologis dan etis yang memampukan kepemimpinan Kristen berakar pada nilai-nilai keadilan dan kemanusiaan. Etika teologis terbukti menjadi fondasi moral yang menuntun pemimpin Kristen untuk mengintegrasikan iman dengan tanggung jawab sosial dan kebangsaan. Dengan demikian, kepemimpinan Kristen berbasis Pancasila berperan sebagai sarana reintegrasi iman dan identitas kebangsaan dalam praksis kehidupan publik Indonesia.